2006
DOI: 10.1007/s10856-006-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface chemistry and topography on the contact guidance of MG63 osteoblast cells

Abstract: The purpose of the present study was to determine in vitro the effects of different surface topographies and chemistries of commercially pure titanium (cpTi) and diamond-like carbon (DLC) surfaces on osteoblast growth and attachment. Microgrooves (widths of 2, 4, 8 and 10 microm and a depth of 1.5-2 microm) were patterned onto silicon (Si) substrates using microlithography and reactive ion etching. The Si substrates were subsequently vapor coated with either cpTi or DLC coatings. All surfaces were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 36 publications
8
74
0
Order By: Relevance
“…Scanning electron microscopic analysis and immunofluorescence of cell morphology identified significant differences in cell shape as a function of both surface chemistry and surface topography, confirming our previous work and the work of others [32,33]. Immunofluorescence images of MG63 cells over the first 24 hours after seeding demonstrated that osteoblasts on smooth and low energy surfaces spread faster than those on rough and higher energy surfaces.…”
Section: Discussionsupporting
confidence: 88%
“…Scanning electron microscopic analysis and immunofluorescence of cell morphology identified significant differences in cell shape as a function of both surface chemistry and surface topography, confirming our previous work and the work of others [32,33]. Immunofluorescence images of MG63 cells over the first 24 hours after seeding demonstrated that osteoblasts on smooth and low energy surfaces spread faster than those on rough and higher energy surfaces.…”
Section: Discussionsupporting
confidence: 88%
“…It is generally accepted that the cell proliferation is optimal on moderately hydrophilic and polar surfaces, which enable adsorption of cell adhesion-mediating extracellular matrix molecules (such as vitronectin, fibronectin, collagen, laminin) in appropriate geometrical conformations, allowing accessibility of specific sites on these molecules to cell adhesion receptors (Chai et al, 2008;Coelho et al, 2010). In accordance with this proposition, the number and spreading of MG 63 cells was higher on micropatterned silicon substrates (grooves of 4, 8 and 10 µm in width) and coated with Ti, which were more hydrophilic and of a higher surface energy than the corresponding micropatterned substrates coated with DLC (Ismail et al, 2007). Also the addition of Ti into DLC films enhanced their attractiveness for cell colonization.…”
Section: Amorphous Carbonsupporting
confidence: 52%
“…Understanding how these facilely modified properties influence cell response aids the development of scaffolds that can promote specific, or specialised, cell function needed for proper tissue functionality and morphogenesis (Ismail et al 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Surface modifications of the biomaterial allow tailoring of surface properties without impact on bulk material properties. Thus, through surface modification, the native surfaces of biomaterials can be physically, or chemically, transformed with the primary goal of engineering desired surface chemistry (Ismail et al 2007), topology (Viswanathan et al 2016), reactivity (Ducheyne and Qui 1999), biocompatibility (Lin et al 2015), hydrophilicity (Yang et al 2002), and/or charge (Courtenay et al 2017).…”
Section: Introductionmentioning
confidence: 99%